2022
DOI: 10.3390/molecules27238286
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Identified Monoterpenoid-Based Small Molecule Able to Support the Survival of Primary Cultured Dopamine Neurons and Alleviate MPTP-Induced Toxicity In Vivo

Abstract: Parkinson’s disease (PD) is the most common age-related movement disorder characterized by the progressive loss of nigrostriatal dopaminergic neurons. To date, PD treatment strategies are mostly based on dopamine replacement medicines, which can alleviate motor symptoms but do not slow down the progression of neurodegeneration. Thus, there is a need for disease-modifying PD therapies. The aim of this work was to evaluate the neuroprotective effects of the novel compound PA96 on dopamine neurons in vivo and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A promising class of compounds on the basis of which highly effective neuroprotective drugs for the treatment of Parkinson’s disease can be developed are monoterpenoids [ 13 , 14 , 15 , 16 ]. Previously, the antiparkinsonian potential of (1R,2R,6S)-3-methyl-6-(prop-1-en-2-yl)cyclohex-3-en-1,2-diol (diol (Prottremin), Figure 1 ) [ 17 , 18 ], which is currently in the first stage of clinical trials, was discovered.…”
Section: Introductionmentioning
confidence: 99%
“…A promising class of compounds on the basis of which highly effective neuroprotective drugs for the treatment of Parkinson’s disease can be developed are monoterpenoids [ 13 , 14 , 15 , 16 ]. Previously, the antiparkinsonian potential of (1R,2R,6S)-3-methyl-6-(prop-1-en-2-yl)cyclohex-3-en-1,2-diol (diol (Prottremin), Figure 1 ) [ 17 , 18 ], which is currently in the first stage of clinical trials, was discovered.…”
Section: Introductionmentioning
confidence: 99%
“…(1S,5S,6R)-2-Methyl-5-(prop-1-en-2-yl)-7-oxabicyclo[4.1.0]hept-2-ene (1S,5S,6R)-4 is described in [28].…”
Section: General Methods and Materialsmentioning
confidence: 99%
“…PA96 displayed this effect at a dose as low as 1 mg/kg, in contrast to the active dose of Prottremine, which is 20 mg/kg. PA96 exhibited an ability to safeguard cultured dopamine neurons from spontaneous and toxin-induced death [28]. While our previous publication primarily focused on the pharmacological implications, we briefly introduced the synthesis of PA96 from epoxide (1S,5S,6R)-4 without delving into the details.…”
Section: Introductionmentioning
confidence: 99%
“…In nerve cells,rotenone inhibits mitochondrial respiratory chain complex I, and subsequently induces reactive oxygen species(ROS) production and mitochondrial dysfunction,leading to the progressive damage of dopaminergic neurons in substantia nigra and stratium [14,15]. Janetzky B et al have found selective loss of respiratory chain complex I in the substantia nigra of PD patients [16].Improtantly,recent studies also found that pathological changes induced by rotenone is not limited to the dopaminergic neurons deterioration [17][18][19],but also includes overactivation of microgial adjacent to the neurons. Sherer TB et al proved that rotenone can activate microglia in rodent PD models before anatomical pathology appears of dopaminergic neurons loss [20].…”
Section: Introductionmentioning
confidence: 99%